SISTEM INFORMASI MANAJEMEN ORGANISASI KEMAHASISWAAN UNIVERSITAS KH A WAHAB HASBULLAH - Yudha Sugianto; Muhyiddin Zainul Arifin; Moh Anshori Aris Widya (KH. A. Wahab Hasbullah University, 2020)
Basically every institution or a university must have an activity, from each activity also has its own field - which is organized as an organization. Each activity also has a flow system of submission and reporting activities that are in the 1 highest field. Neither in a Universiatas or a Higher Education must also have activities where in every activity is under the Student Affairs. One of the fields in the University is the Student Executive Board (BEM), this field has the duty to run activities of the University that has been agreed upon rakorgram, this field can be regarded as a government agency of the University and for the field that oversees the submission of programs or activities is the Council Student Representative (DPM). In every activity has a working system which will have activity submission and activity reporting from that activity will be reported to student affairs. So far, the system of filing and reporting activities are still printing or can still be said to be manual. A systematic or computerized management system is required in this activity to reduce the collection of files by paper or manual. Based on the description, the author took a study entitled